Acute fibrinous and organizing pneumonia after lung transplantation: A case report of treatment with infliximab and tocilizumab and literature review - Christophe Abellan; Foteini Ioakeim; Alessio Casutt; Benoit Lechartier; Zisis Balmpouzis; Samuel Rotman; Leslie Noirez; Isabelle Rochat; John-David Aubert; Angela Koutsokera (Respiratory Medicine Case Reports)
Introduction: Acute fibrinous and organizing pneumonia (AFOP) is a severe form of acute lung injury which can occur after lung transplantation. Treatment is empiric, based on immunosuppressive regimens and the mortality rate is very high. Case presentation: We report the case of a young lung transplant (LT) recipient who developed AFOP following a respiratory viral infection while on suboptimal maintenance immunosuppression due to adherence issues. Diagnosis was confirmed by cryobiopsies showing intra-alveolar fibrin balls. Despite high dose systemic corticosteroids, the patient developed severe respiratory failure requiring mechanical ventilation. IV infliximab and tocilizumab were administered. The patient was extubated 11 days later and discharged to home 42 days after intubation with 1L/min O2. She developed severe pleuritic pain needing opioid treatment and died 4 months later. Conclusion: While high-dose systemic corticosteroids remain the first line of treatment, the use of anti TNF-α has shown promising results in case reports. Furthermore, we propose prompt realization of a cytokine panel analysis in both blood and bronchoalveolar lavage to better guide the adjuvant administration of a targeted anti-inflammatory therapy.